The Impact of a Volleyball-Specific Fatigue Protocol on the Balance, Proprioception, and Performance of Volleyball Players at High and Low Risk for ACL Injuries - Hamid Alizadeh Darabi; Ebrahim Mohammad Ali Nasab Firouzjah; Sajad Roshani (Journal of Rehabilitation Sciences and Research)
Background: This study aimed to assess the impact of a volleyball-specific fatigue protocol on balance, proprioception, and performance in volleyball players with differing ACL injury risk levels. Methods: his semi-experimental research utilized a pre-test-post-test design. Forty volleyball players from Urmia were selected and divided into low- and high-risk groups based on ACL injury potential, assessed using the Landing Error Scoring System (LESS). A LESS score below 6 indicated low risk, while above 6 indicated high risk. Balance was measured using the stork test (static balance) and Y balance test (dynamic balance), knee proprioception was assessed with a goniometer, and performance was evaluated with the Sargent jump test. After baseline assessments, players were subjected to a volleyball-specific fatigue protocol, after which all tests were repeated. Analysis of covariance and dependent t-tests were used to evaluate inter-group and intra-group differences. Results: The dependent t-tests and analysis of covariance indicated that fatigue significantly decreased static balance (P=0.001, P=0.001), dynamic balance (P=0.001, P=0.001), and performance (P=0.001, P=0.001). Wilcoxon and Mann-Whitney U tests also significantly reduced proprioception post-fatigue (P=0.001, P=0.001). Additionally, significant differences were found between the groups for all variables (P<0.05) except for proprioception (P>0.05). Conclusion: Overall, the findings suggest that fatigue is a significant factor in reducing balance, proprioception, and explosive power. This decline was greater in the high-risk injury group, likely due to baseline neuromuscular weaknesses in this group.